Trabajo colaborativo: una experiencia desde el aula de pre grado - Vásquez Paulini, Luis (2017)
This article reports the experiences from the A and B undergraduate classes of the last eight years, with the aim of showing the effectiveness of collaborative work as a group didactic strategy that promotes learning and skill development. The experiences were developed and continue to be applied in the different subjects held in the Pre-Grade classrooms at the Faculty of Education and Psychology of the Marcelino Champagnat University of Surco-Lima Peru. Our account of them is just one of the many possible stories in the way of constructing didactic activities, which allow us to develop skills, positive interdependence and at the same time learning the contents. We conclude with the wish that other teachers of the university share their experiences of research and teaching in the classroom, which allow us to build our particular theoretical-methodological journey in the pre-grade classrooms.